Pengaruh Pelatihan Kerja terhadap Produktivitas Karyawan di Kalangan Gen Z pada Perusahaan Pizza Hut Kota Samarinda - Mochammad Hisyaam Darwin; Achmad Efendi; Jubaidi, Jubaidi (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze the effect of job training on the productivity of Generation Z employees at Pizza Hut Samarinda City. In the highly competitive and dynamic fast food industry, job training is a strategic element in improving competence, work effectiveness, and competitiveness of human resources. This is increasingly important for Generation Z employees, who are known to be adaptive to technology and have different learning styles compared to previous generations. This study uses a quantitative approach with the saturation sampling method, involving 55 respondents from Generation Z who are actively working in the company. The data collection technique was carried out through a closed questionnaire with a Likert scale, and the data were analyzed using SPSS software version 27. The results showed that job training had a positive and significant effect on employee productivity, with a regression coefficient of 0.728 and a significance value of 0.000. The coefficient of determination (R²) of 0.528 indicates that 52.8% of the variation in employee productivity can be explained by job training. The quality of training materials and evaluation factors were identified as the most dominant aspects in increasing productivity. These findings emphasize the importance of designing relevant, digital-based training programs that are tailored to the characteristics of the younger generation. This research is expected to contribute to the development of human resources in the fast food sector and become a reference in designing effective training policies in the modern era.